Transient Bacteremia Promotes Catheter-Related Central Venous Thrombosis through Neutrophil Extracellular Traps - Chen, Jeng-Wei; Hsu, Chih-Chieh; Su, Chien-Chia; Hsu, Ron-Bin; Chiu, Yen-Ling; Jung, Chiau-Jing; Chia, Jean-San (Thrombosis and Haemostasis, 2022)
Formation of intravenous catheter-related thrombosis leads to central venous stenosis in patients requiring renal replacement therapy or chemotherapy infusion, yet the triggers or mechanisms remain unclear, especially in patients without symptoms of infection. In this study, we found that neutrophil extracellular traps (NETs) could be detected in the fibrin sheaths from dialysis patients without clinical manifestations of infection. Confocal microscopy revealed bacteria imbedded in NETs in the fibrin sheaths. Thirty-nine of 50 (78%) fibrin sheath specimens contained bacteria detectable by 16S ribosomal RNA genome typing with a predominance of Staphylococcus aureus (69%). In rat models, transient bacteremia of S. aureus induced NETs in enlarged fibrin sheaths, and treatment with DNase I alone significantly reduced both NET and fibrin sheath formation surrounding the catheter. Therefore, transient bacteremia could be a silent trigger that induces NET-related immunothrombosis enhancing catheter-related central venous stenosis.
Keywords: transient bacteremia; neutrophil extracellular traps; Staphylococcus aureus; catheter-related central venous thrombosis